Baseline characteristics in the SYNCHRONIZE-2 randomized phase 3 trial of survodutide, a glucagon receptor/GLP-1 receptor dual agonist, for obesity in people with type 2 diabetes - Wharton, Sean; le Roux, Carel W.; Bozkurt, Biykem; Platz, Elke; Bleckert, Gabriele; Ajaz Hussain, Samina; Brückmann, Martina; Startseva, Elena; Kloer, Isabel M.; Kaplan, Lee M. (Diabetes, obesity and metabolism, 2025)
Abstract Aims Survodutide is an investigational glucagon receptor/glucagon-like peptide-1 receptor dual agonist that has shown promise for treating obesity and its complications in Phase 2 trials. Two double-blind, randomized, global Phase 3 trials are designed to assess the efficacy and safety of survodutide for treatment of obesity?SYNCHRONIZE?-1 in people with obesity without type 2 diabetes (T2D) and SYNCHRONIZE?-2 in people with obesity and T2D. This paper describes the baseline characteristics of participants in SYNCHRONIZE-2 (ClinicalTrials.gov identifier NCT06066528). Materials and Methods Participants aged ≥18?years with a body mass index (BMI) ≥27?kg/m2 and T2D were randomized 1:1:1 to weekly subcutaneous survodutide (up-titrated to 3.6 or 6.0?mg) or placebo with recommendations for modified diet and physical activity. The primary endpoints are the percentage change in body weight (BW) and achievement of BW reduction of ≥5% from baseline to Week 76. Results SYNCHRONIZE-2 includes 752 treated participants from 133 sites across 19 countries. At baseline, participants had a mean age of 55.7?years, BMI 36.5?kg/m2, BW 104.1?kg, waist circumference 115.5?cm and haemoglobin A1c 7.4%; 50.7% were female. Overall, 36.2% are from Europe, 32.8% from North America and 22.3% from East Asia. The most common obesity complications included hypertension (69.0%), dyslipidaemia (67.6%), obstructive sleep apnoea (17.3%) and arteriosclerotic cardiovascular disease (10.9%); 78.7% were treated with metformin, 34.2% with sodium-glucose co-transporter-2 inhibitors and 58.6% with lipid-lowering medications. Conclusions SYNCHRONIZE-2 will determine the efficacy, safety and tolerability of survodutide for BW reduction in people with obesity and T2D, whose baseline characteristics suggest a representative, diverse cohort.